2006
DOI: 10.1111/j.1439-0264.2006.00698.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related Changes in the Number of Mast Cells in the Avian Lymphoid Organs

Abstract: The distribution of mast cells (MCs) was studied in the lymphoid organs (thymus, bursa of Fabricius and spleen) of 0-, 7-, 21-, 30- and 120-day-old chickens, using light microscopic histochemical techniques. Tissues samples were obtained under deep anaesthesia from animals in five groups. Tissues were fixed in Mota's fixative (basic lead acetate) for 24 h and embedded in paraffin. Six-micrometre-thick sections were stained with toluidine blue in 0.5% aqueous solution at pH 1.0 for 5 min and Alcian blue/Safrani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
3
5
0
2
Order By: Relevance
“…Their number increased as the age advances in both the sexes as mentioned by Vijayaragavan (1988) in White Leghorn chicken. Mast cells density was higher in close proximity to the arterial vessels and medullary region of thymus than in the cortical region as stated by Karaca et al, (2006) in chicken and Leena et al, (2008) in Giriraja birds.…”
Section: Resultssupporting
confidence: 69%
“…Their number increased as the age advances in both the sexes as mentioned by Vijayaragavan (1988) in White Leghorn chicken. Mast cells density was higher in close proximity to the arterial vessels and medullary region of thymus than in the cortical region as stated by Karaca et al, (2006) in chicken and Leena et al, (2008) in Giriraja birds.…”
Section: Resultssupporting
confidence: 69%
“…In the present studies, researchers were seen alcian blue‐positive mast cells while they were not seen pink‐red colour safranin mast cells on lymphoid organs in turkey (Karaca, Yörük, & Uslu, ), avian lymphoid organs (Karaca, Yörük, & Uslu, ) and caecum of quail (Yıldız et al., ). In the study on the chicken tongue (Karaca & Yörük, ), sow oviduct (Özen et al., ), bovine reproductive tract (Saruhan, Sağsöz, & Akbalık, ) and quail lungs (Harem, Liman, & Alan, ) were reported that mast cells were located different area.…”
Section: Discussionsupporting
confidence: 37%
“…Mast cells may produce, store, and release a large number of bioactive and vasoactive mediators that continuously modulate the tissues in which they are located (19). The number and density of mast cells in tissues vary depending on factors such as age and pathogens (20). Mast cells can reside in all layers of the gastrointestinal tract, but most of them are found in the lamina propria of the mucosa and the submucosa (21).…”
Section: Discussionmentioning
confidence: 99%